ANALISIS TERMOHIDROLIKA TERAS REAKTOR SUSUNAN HEKSAGONAL - S, Adolf Asih; Suwono, Aryadi; Hardianto, Toto (Mesin, 1998)
In this experiment, the study focusses on reactor core thermohydraulic aspects especially the distributions of fuel surface temperature, ï¬uid temperature and ï¬uid axial velocity. Simulation data were obtained in the middle, at the edge and at the comer sub-channels. In this experiment, modeling of hexagonal conï¬guration of reactor core and reï¬ector was carried out. The power generations were assumed constant at 250 kwatt, 375 kwatt and 5 00kwatt for each ï¬lel element. This model was prepared and analyzed using Fluent Version 4.25 package program available at the Thermodynamic Laboratory of IURC-ES. The result shows that this reactor core model gives low fuel surface and fluid temperatures.